The Relationship between English Language Learning Beliefs and English Academic Achievement among the English Major Students of IAIN Samarinda - Hayati, Noor (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2020)
AbstractEnglish as an international language has been learned for various purposes. However, not all students can achieve their goals in learning English, one of many factors influencing their success in learning English is their own beliefs. This research aimed at investigating students’ beliefs about English language learning and English academic achievement. Descriptive and correlation design, quantitative method was applied in this research. The English scores of 50 fifth-semester students of IAIN Samarinda and their responses to Beliefs About Language Learning Inventory (BALLI) were analyzed using descriptive statistics and Pearson Product Moment correlation. The results showed that the beliefs about motivation and expectation were the one mostly held by the students, followed by the nature of language learning, learning and communication strategies, foreign language aptitude, and the difficulty of language learning. There was positive and strong correlation between students’ beliefs about language learning and their English academic achievement (r = .597).Keywords: BALLI, English academic achievement, English language learning beliefs AbstrakBahasa Inggris sebagai bahasa internasional telah dipelajari untuk berbagai tujuan. Namun, tidak semua siswa dapat mencapai tujuannya dalam belajar bahasa Inggris, salah satu faktor yang mempengaruhi keberhasilan mereka dalam belajar bahasa Inggris adalah keyakinan mereka sendiri. Penelitian ini bertujuan untuk mengetahui keyakinan siswa tentang pembelajaran bahasa Inggris dan prestasi akademik bahasa Inggris. Desain deskriptif dan korelasi, metode kuantitatif digunakan dalam penelitian ini. Nilai bahasa Inggris 50 mahasiswa semester lima IAIN Samarinda dan tanggapan mereka terhadap Beliefs About Language Learning Inventory (BALLI) dianalisis menggunakan statistik deskriptif dan korelasi Product Moment Pearson. Hasil penelitian menunjukkan bahwa keyakinan tentang motivasi dan harapan paling banyak dianut oleh siswa, diikuti oleh sifat belajar bahasa, strategi pembelajaran dan komunikasi, bakat bahasa asing, dan kesulitan belajar bahasa. Ada korelasi positif dan kuat antara keyakinan siswa tentang pembelajaran bahasa dan prestasi akademik bahasa Inggris mereka (r = .597).Kata kunci: BALLI, Prestasi akademik bahasa Inggris, keyakinan belajar bahasa Inggris